A target‐oriented solid‐gas thermochemical sorption heat transformer for integrated energy storage and energy upgrade. Issue 4 (29th August 2012) - Li, Tingxian; Wang, Ruzhu; Kiplagat, Jeremiah K.
<x xml:space="preserve">Abstract</x> An innovative target‐oriented solid‐gas thermochemical sorption heat transformer is developed for the integrated energy storage and energy upgrade of low‐grade thermal energy. The operating principle of the proposed energy storage system is based on the reversible solid‐gas chemical reaction whereby thermal energy is stored in form of chemical bonds with thermochemical sorption process. A novel thermochemical sorption cycle is proposed to upgrade the stored thermal energy by using a pressure‐reducing desorption method during energy storage process and a temperature‐lift adsorption technique during energy release process. Theoretical analysis showed that the proposed target‐oriented thermochemical sorption heat transformer is effective for the integrated energy storage and energy upgrade, and the low‐grade thermal energy can be upgraded from 87 to 171°C using a group of sorption working pair MnCl2‐CaCl2‐NH3. Moreover, it can give the flexibility of deciding the temperature magnitude of energy upgrade by choosing appropriate sorption working pairs. © 2012 American Institute of Chemical Engineers AIChE J, 59: 1334–1347, 2013